2008
DOI: 10.1080/07357900701788106
|View full text |Cite
|
Sign up to set email alerts
|

Urocortin's Inhibition of Tumor Growth and Angiogenesis in Hepatocellular Carcinoma via Corticotrophin-Releasing Factor Receptor 2

Abstract: Urocortin (UCN) functions via corticotrophin-releasing factor receptors (CRFRs), CRFR1 & 2. CRFR2 is reported to be a tonic suppressor of vascularization, implying its role in tumor angiogenesis. Here, it was found that UCN inhibited the growth of hepatocellular carcinoma (HCC) and reduced tumor microvessel density in nude mice. Hepatoma cells didn't express CRFRs whereas vessels expressed CRFRs, mainly CRFR2. In vitro three-dimensional culture assay showed UCN inhibited angiogenesis, this effect was abolished… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
1
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 24 publications
2
36
1
1
Order By: Relevance
“…For instance, Ucn inhibited angiogenesis through activation of CRF 2 receptor and subsequently suppressed the growth of hepatocellular carcinoma as well as small cell lung carcinoma cells. 54,55 Moreover, almost complete loss of CRF 2 expression in hypervascularized renal cell carcinoma supported an idea of CRF 2 as an endogenous inhibitor of angiogenesis. 56 Similarly, loss of CRF 2 receptor expression was observed in vascular endothelial cells of prostate cancer tissue not in normal prostate tissue.…”
Section: 51mentioning
confidence: 72%
“…For instance, Ucn inhibited angiogenesis through activation of CRF 2 receptor and subsequently suppressed the growth of hepatocellular carcinoma as well as small cell lung carcinoma cells. 54,55 Moreover, almost complete loss of CRF 2 expression in hypervascularized renal cell carcinoma supported an idea of CRF 2 as an endogenous inhibitor of angiogenesis. 56 Similarly, loss of CRF 2 receptor expression was observed in vascular endothelial cells of prostate cancer tissue not in normal prostate tissue.…”
Section: 51mentioning
confidence: 72%
“…78 These data suggested a receptor-mediated paracrine involvement in local inflammatory phenomena within the liver. Furthermore, an antitumor effect of Ucn in HCC and in tumors growing in rodents has been demonstrated, via activation of CRF2, which inhibited cell growth and angiogenesis, 101 whereas a CRFbased apoptosis-regulating mechanism was shown in obstructive jaundice challenged liver, but not under basal conditions (Table 1). 76 These findings, although limited, advocate a potential regulatory role of the CRF system in the liver, regarding immunological functions, apoptotic mechanisms as well as oncogenic, antitumor and neoangiogenic processes.…”
Section: Future Prospectsmentioning
confidence: 99%
“…[97][98][99][100] These antitumor findings were also tested in a study showing a role of hepatic CRF receptors on tumor growth and angiogenesis. 101 Both in vivo and in vitro effects of Ucn1 were evaluated in human hepatoma cell lines SMMC-7721 and HepG2, human umbilical vein endothelial cells (HUVECs) and human hepatocellular carcinoma tissues. Ucn 1 inhibited the growth of hepatocellular carcinoma and reduced tumor microvessel density in nude mice.…”
mentioning
confidence: 99%
“…Recently, increased interest has been developing in the expression and biological role of the CRH system in malignant tumors. Several lines of evidence have indicated that CRH inhibited human endometrial adenocarcinoma cell growth (Graziani et al 2002) and that Ucn1 inhibited hepatocellular carcinoma growth and angiogenesis (Bale et al 2002, Wang et al 2008. Rassouli et al (2011) suggested that dermal fibroblasts, deficient in CRH (CRHK/K), had higher proliferation and migration rates compared with WT (CRHC/C) cells.…”
Section: Introductionmentioning
confidence: 99%